CD13 deficiency leads to increased oxidative stress and larger atherosclerotic lesions. (August 2019) - Devarakonda, Charan V.; Pereira, Flavia E.; Smith, Jonathan D.; Shapiro, Linda H.; Ghosh, Mallika
Abstract: Background and aims: Atherosclerosis is an inflammatory cardiovascular disorder characterized by accumulation of lipid-loaded macrophages in the intima. Prolonged accumulation leads to apoptosis of macrophages and eventually to progression of lesion development. Prevention of macrophage accumulation within the intima has been shown to reduce lesion formation. Since CD13 mediates trafficking of macrophages to sites of injury and repair, we tested the role of CD13 in atherosclerosis. Methods: CD13 +/+ Ldlr −/− and CD13 −/− Ldlr −/− (low density lipoprotein receptor) mice were fed basal or high fat diet (HFD) for 9, 12 and 15 weeks. Mice were euthanized and aortic roots along with innominate arteries were analyzed for atherosclerotic lesions. Cellular mechanisms were determined in vitro using CD13 +/+ and CD13 −/− bone marrow derived macrophages (BMDMs) incubated with highly oxidized low-density lipoprotein (oxLDL). Results: At the 9 and 12 week time points, no differences were observed in the average lesion size, but at the 15 week time point, CD13 −/− Ldlr −/− mice had larger lesions with exaggerated necrotic areas. CD13 +/+ and CD13 −/− macrophages endocytosed similar amounts of oxLDL, but CD13 −/− macrophages generated higher amounts of oxidative stressors in comparison to CD13 +/+ macrophages. This increased oxidative stress was due to increased nitric oxide production in oxLDL treated CD13 −/− macrophages. Accumulated oxidative stress subsequently led to accelerated apoptosis and enhanced necrosis of oxLDL treated CD13 −/− macrophages. Conclusions: Contrary to our prediction, CD13 deficiency led to larger atherosclerotic lesions with increased areas of necrosis. Mechanistically, CD13 deficiency led to increased nitric oxide production and consequently, greater oxidative stress. Graphical abstract: Image 1 Highlights: CD13 deficiency in bone marrow derived macrophages led to increased nitric oxide production (oxidative stress) with oxLDL treatment. Increased oxidative stress in CD13 deficient bone marrow derived macrophages led to amplified apoptosis. Absence of CD13 led to larger atherosclerotic lesions in high fat diet-fed CD13 −/− Ldlr −/− mice. Atherosclerotic lesions from CD13 −/− Ldlr −/− mice contained higher number of apoptotic cells.